2019
DOI: 10.2147/ijn.s215717
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Clinical Implication of Vitamin D Nanomedicine for Peritoneal Dialysis-Related Peritoneal Damage</p>

Abstract: PurposeVitamin D is a novel potential therapeutic agent for peritoneal dialysis (PD)-related peritoneal fibrosis, but it can induce hypercalcemia and vascular calcification, which limits its applicability. In this study, we create nanotechnology-based drug delivery systems to investigate its therapeutics and side effects.Materials and methods1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N- [amino-(polyethylene glycol)2000] (DSPE-PEG) and L-α-phosphatidylcholine (PC), which packages with 1α,25(OH)2D3, were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In our previous study, we found that Ab-Vit.D-MNPs had the same therapeutic effect as vitamin D3 in vitro. 13 Therefore, in this study, we investigated its therapeutic effect in vivo. The results showed that Vit.D-MNPs conjugated with an antibody against GPM6A, a peritoneal marker, enhanced peritoneum targeting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we found that Ab-Vit.D-MNPs had the same therapeutic effect as vitamin D3 in vitro. 13 Therefore, in this study, we investigated its therapeutic effect in vivo. The results showed that Vit.D-MNPs conjugated with an antibody against GPM6A, a peritoneal marker, enhanced peritoneum targeting.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we constructed vitamin D-liposomal NPs and examined their therapeutic effects in vitro. 13 The results showed that these NPs were taken up by mesothelial cells and did not cause cell toxicity as well as provided the same therapeutic effect as vitamin D3. However, the therapeutic effects of these NPs in vivo are still unknown.…”
Section: Introductionmentioning
confidence: 91%
“…In other study, L-α-phosphatidylcholine which packages with 1α,25(OH)2D3, and 1,2-distearoyl-snglycero-3-phosphoethanolamine-N-[amino-(polyethylene glycol)2000], were used to produce nontoxic and biocompatible vitamin D nanoliposomes. 149 Moreover, in spite of biocompatibility properties of liposomes, these formulations could decrease the toxicity of antimicrobial agent which are potentially toxic. 145…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Excessive Cal administration can result in side effects including hypercalcemia, vascular calcification, and anaphylaxis, primarily because the drug shows nonselective distribution in vivo. 22 , 23 , 24 , 25 , 26 One of the major challenges with Cal for breast cancer investigations therefore is achieving a sufficiently high drug concentration within cancer cells. Delivering Cal via nanoscale drug delivery systems (DDSs) may overcome this, as DDSs have often proven successful at targeting drugs to tumors via active targeting mechanisms or passive targeting mechanisms like the enhanced permeability and retention effect.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive Cal administration can result in side effects including hypercalcemia, vascular calcification, and anaphylaxis, primarily because the drug shows nonselective distribution in vivo 22–26 . One of the major challenges with Cal for breast cancer investigations therefore is achieving a sufficiently high drug concentration within cancer cells.…”
Section: Introductionmentioning
confidence: 99%